HOW LOCAL SOCIAL SERVICE DELIVERY PANDEMIC LESSONS MIGHT SHAPE POST-COVID REALITIES - Schmid, Jeanette; Bradley, Holly (Canadian Social Work Review / Revue canadienne de service social, 2022)
This contribution considers the ways in which COVID-19 impacted social service delivery in the central Vancouver Island region over 18 months after the declaration of the pandemic. Significant shifts in the external and internal environment were made to accommodate requirements of public health orders, ensure safety in service, and respond to the heightened needs of certain sectors of the population. The impact had a different character for each of six-month tranches studied. Lessons for a post – COVID-19 future include: make micro- to macro-level shifts that allow room for rapid adaptation; facilitate inclusion, especially of those most marginalized; and ensure ongoing reflection. This involves keeping in mind the needs of service users, service providers, and the community.